2021
DOI: 10.1186/s40359-021-00565-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on mental health in the general population: a comparison between Germany and the UK

Abstract: Background The COVID-19 pandemic has led to dramatic social and economic changes in daily life. First studies report an impact on mental health of the general population showing increased levels of anxiety, stress and depression. In this study, we compared the impact of the pandemic on two culturally and economically similar European countries: the UK and Germany. Methods Participants (UK = 241, German = 541) completed an online-survey assessing C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 55 publications
4
49
1
1
Order By: Relevance
“…Size and proportions of the group. More participation of women in voluntary studies on psychological effects of the COVID-19 pandemic is rather a standard, not an exception (Dębski et al 2021;Fullana et al 2020;Juchnowicz et al 2021;Knolle et al 2021;Nikolaidis et al 2021;Padmanabhanunni and Pretorius 2021;Palgi et al 2020;Pierce et al 2020), not meaning that we are unaware of the limitations of conclusions caused by this situation. The number of respondents we obtained was generally low, although sufficient to test the formulated hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Size and proportions of the group. More participation of women in voluntary studies on psychological effects of the COVID-19 pandemic is rather a standard, not an exception (Dębski et al 2021;Fullana et al 2020;Juchnowicz et al 2021;Knolle et al 2021;Nikolaidis et al 2021;Padmanabhanunni and Pretorius 2021;Palgi et al 2020;Pierce et al 2020), not meaning that we are unaware of the limitations of conclusions caused by this situation. The number of respondents we obtained was generally low, although sufficient to test the formulated hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies into the Covid-19 pandemic have also shown negative impact of the outbreak and the following restrictions on physical and mental health in general populations, resulting in e.g. increased levels of stress, anxiety, and symptoms of depression, [10][11][12][13][14][15][16] as well as negative economic consequences and societal disruptions [17]. However, a review and meta-analysis concluded that the psychological impact from the Covid-19 lockdown on general populations was small and highly heterogeneous [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the United Kingdom, where lockdown was came into force somewhat later than in other countries in the European Union and funding of preventive measures was ten times lower compared to Germany, a more severe direct impact of COVID-19 on health, financial situation and families. By contrast, people in Germany were less optimistic regarding the end of the epidemic, but more worried about their life [ 15 ]. Another study that compared people in Poland and China found that less strict demand for face masks use in Poland compared to China was associated with more intense anxiety, depression and stress, as well as physical symptoms related to the COVID-19 infection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%